Stars of the masculinity and Masculinity of the stars - Hasan Chavoshian; Seyed Javad Hosseini Rasht Abadi (Taḥqīqāt-i Farhangī-i Īrān)
Change in social relations may challenge superiority of men over women; so men will need an ideology that reestablishes their superiority whenever such “crisis tendencies” happen. This ideology recommends an “Ideal Masculinity” and reestablishes “normal” pattern of manhood. Rawean Connell dubs it as “Hegemonic masculinity” (HM) and believes that because of endless pressure of illegitimating factors, “HM” will be in change forever. By application of the Connell\'s theories and Weberian qualitative approach, first of all a “basic ideal type of masculinity” was constructed from encouraged religious-revolutionary values in the movies and propaganda of the first years after revolution; then masculine values which were celebrated and admired in the best seller movie of every year during 1979_2007, were compared by this “basic ideal type”. Comparison of the 32 concluded “ideal types” indicated that serious interruption took place in three years (1989, 1997, and 2002). Then ideal type of each era was constructed and was compared with each other. Results of this comparison approve Connell\'s theory about changeability of the HM in accordance with the social changes.